BLENDED CONSTRUCTIVE LEARNING MODEL FOR FACING THE FOURTH INDUSTRIAL REVOLUTION - Yeni Erita; Silvi Hevria; Rifda Eliyasni; Wirda (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The appropriate learning approach used in this digital era (industry 4.0) is blended learning (on-line). This research started from analyzing the needs of teachers and students and then designed a new model that fitted the desired needs both teachers and students. After designing the model, it was implemented then evaluated the results of the process that has been carried out. The purpose of this research was to see an appropriate model dealing with the fourth industrial revolution. The method used in this research was a quantitative descriptive method using descriptive statistical data analysis with the percentage formula. The results obtained in this study on practicality obtained very practical results, while the effectiveness of the results obtained experienced a very significant increase from 44.7 to 85.3 in terms of style understanding, the second material from 33.33 to 80 on various styles (muscle force, electric force, magnetic force, gravitational force and frictional force), and on the material the benefits of that force in daily life from 29.2 to 83.33.